Relationship length weight and condition factors of mackerel (Rastrelliger kanagurta) landed in Tanjung Tiram Port Batu Bara District North Sumatra Province - Sihombing, Gokma David Lefi; Handoco, Ewin; Manik, Ria Retno Dewi Sartika (Sam Ratulangi University, 2024)
This research aims to determine growth patterns and condition factors. Apart from that, it is also to determine the level of gonad maturity and the gonad maturity index. The method used was a quantitative descriptive method by measuring length and weight and then dissection was carried out to observe the level of gonad maturity of male mackerel fish samples landed every week. The number of samples obtained during the August-September 2023 period was 200 individuals. The results of the research show that the equation for the relationship between length and weight is W = 0,00003L²͐⁸⁴⁵⁴⁷, which indicates a negative allometric growth pattern. The highest condition factor was obtained in the 190-191 mm length class with an average of 0,8757 and the lowest in the 185-186 length class with an average of 0,8416. The gonad maturity level of mackerel (Rastrelliger kanagurta) consists of TKG I to TKG IV. The IKG value obtained ranged from 5,616 to 6,375%. The increase in length of male mackerel shows a weak correlation with weight. Meanwhile, the weight of male mackerel had a significant influence on IKG. Keywords: Male mackerel, growth, condition factors, TKG, IKG. Abstrak Penelitian ini bertujuan untuk mengetahui pola pertumbuhan dan faktor kondisi. Selain itu juga untuk mengetahui tingkat kematangan gonad dan indeks kematangan gonad. Metode yang dilakukan adalah metode deskriptif kuantitatif dengan mengukur panjang dan berat kemudian dilakukan pembedahan untuk diamati tingkat kematangan gonad sampel ikan kembung lelaki yang didaratkan setiap minggunya. Adapun jumlah sampel yang diperoleh selama periode agustus-september 2023 adalah sebanyak 200 ekor. Hasil penelitian menunjukkan bahwa persamaan hubungan panjang berat W = 0,00003L²͐⁸⁴⁵⁴⁷ yang menunjukkan pola pertumbuhan allometrik negatif. Faktor kondisi tertinggi diperoleh pada kelas panjang 190-191 mm dengan rata-rata sebesar 0,8757 dan terendah pada kelas panjang 185-186 dengan rata-rata sebesar 0,8416. Tingkat kematangan gonad ikan kembung (Rastrelliger kanagurta) terdiri dari TKG I sampai TKG IV. Nilai IKG yang didapatkan berkisar 5,616-6,375%. Pertambahan ukuran panjang ikan kembung lelaki menunjukkan korelasi yang lemah terhadap berat. Sedangkan berat ikan kembung lelaki memberikan pengaruh yang nyata terhadap IKG. Kata Kunci: Ikan kembung lelaki, pertumbuhan, faktor kondisi, TKG, IKG.